A Very Short, Fairly Interesting and Reasonably Cheap Book about Management Theory - Bridgman, Todd (SAGE Publications, Ltd. (UK), 2020)
Conceived by Chris Grey, the Very Short, Fairly Interesting and Reasonably Cheap series offers an antidote to conventional textbooks. Each book takes a core area of the curriculum and turns it on its head by providing a critical and sophisticated overview of the key issues and debates in an informal, conversational and often humorous way. In Management Theory, Todd Bridgman and Stephen Cummings uncover enduring myths about famous theorists, from Adam Smith and Max Weber to Frederick Taylor, Mary Parker Follett, Abraham Maslow and Kurt Lewin. By exploring how these myths became cast as the foundations of management, this accessible and engaging book generates new ways of thinking about what management could be today and in the future. Students can head to YouTube to watch a selection of specially-curated, bitesize videos - 20 Insights on Management Theory - which explain key topics relating to management theory. Lecturers can visit https://study.sagepub.com/bridgman to access a range of PowerPoint slides that can be used in their teaching.